Bioprospeksi Ekstrak Biji dan Daun Mahoni serta Filtrat Bakteri Endofit untuk Pengendalian Meloidogyne incognita: Bioprospection of Mahogany Seed and Leaf Extracts and Endophytic Bacterial Filtrate to Control Meloidogyne incognita - Shafira, Novia Sarah; Munif, Abdul; Supramana (Jurnal Fitopatologi Indonesia, 2026)
Bioprospection of Mahogany Seed and Leaf Extracts and Endophytic Bacterial Filtrate to Control Meloidogyne incognita The root knot nematode Meloidogyne incognita is a major pathogen of tomato plants and causes yield losses of up to 77%. This study aimed to evaluate the effectiveness of mahogany seed and leaf extracts and endophytic bacterial filtrates against the nematode M. incognita in tomato plants at laboratory and greenhouse scales. Secondary metabolite compound analysis was carried out using gas chromatography-mass spectrometry (GC-MS). The final concentrations of mahogany seed and leaf extracts obtained based on LC95 values were 9.429% and 27.448%. Filtrates from three endophytic bacterial isolates were tested for their mortality against juvenile 2 (J2) M. incognita. One endophytic bacterial isolate, i.e. APE 35 was found to cause the highest mortality. Mahogany seed and leaf extracts and endophytic bacterial filtrate APE 35 can suppress root knots in tomato plants caused by M. incognita. Mahogany seed extract treatment can suppress root knots with the highest percentage, i.e. 66.23%. However, mahogany seed and leaf extracts can be phytotoxic and inhibit the growth of tomato plants. Mahogany seed and leaf extracts, as well as the endophytic bacterial filtrate APE 35, contain compounds with potential nematicidal properties. Mahogany seed extract contains the highest nematicidal compounds, namely n-Hexadecanoic acid (17.71%) and 9,12-Octadecadienoic acid (Z,Z) (1.81%).